2013
DOI: 10.1007/s11999-012-2656-1
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Stabilization for Bone Metastases, Myeloma, or Lymphoma: Do We Need to Protect the Entire Bone?

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 9 publications
8
72
0
3
Order By: Relevance
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure also enables the surgeon to remove all gross disease, minimize recurrence and hardware failure, and protect the rest of the femur against progressing disease [2]. Disadvantages of endoprosthetic reconstruction include hip dislocation, leg length discrepancy, blood loss during the procedure, and intraoperative hypotension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramedullary nailing traditionally has been an accepted form of palliative treatment for patients with metastatic carcinoma, but we could find no studies that report specifically on intramedullary nailing of metastatic sarcoma lesions. Questions/purposes We asked: (1) What is the survival of patients with an impending or pathologic fracture from a sarcoma metastasis? (2) What proportion of patients treated with intramedullary nailing subsequently underwent a revision procedure or nail removal during their lifetimes?…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, Price and colleagues reported transient cardiopulmonary derangements, but concluded that long-stem femoral implants are an appropriate surgical option, and remain their preference. However, another recent CORR 1 publication [1] found a lack of disease progression in patients with tumors other than myeloma and renal cell carcinoma, along with a similar rate of physiologic nonfatal complications. This led the senior author to state in the Editor's Spotlight/Take 5 interview [2], ''I have been less aggressive with putting in long-stem cemented femoral components that protect the entire femur.''…”
mentioning
confidence: 98%